Quantitative ultrasound of cortical bone in the femoral neck predicts femur strength: Results of a pilot study. (15th January 2013) - Grimal, Quentin; Grondin, Julien; Guérard, Sandra; Barkmann, Reinhard; Engelke, Klaus; Glüer, Claus‐C; Laugier, Pascal
Abstract: A significant risk of femoral neck (FN) fracture exists for men and women with an areal bone mineral density (aBMD) higher than the osteoporotic range, as measured with dual‐energy X‐ray absorptiometry (DXA). Separately measuring the cortical and trabecular FN compartments and combining the results would likely be a critical aspect of enhancing the diagnostic capabilities of a new technique. Because the cortical shell determines a large part of FN strength a novel quantitative ultrasound (QUS) technique that probes the FN cortical compartment was implemented. The sensitivity of the method to variations of FN cortical properties and FN strength was tested. Nine femurs (women, mean age 83 years) were subjected to QUS to measure the through transmission time‐of‐flight (TOF) at the FN and mechanical tests to assess strength. Quantitative computed tomography (QCT) scans were performed to enable analysis of the dependence of TOF on bone parameters. DXA was also performed for reference. An ultrasound wave propagating circumferentially in the cortical shell was measured in all specimens. Its TOF was not influenced by the properties of the trabecular compartment. Averaged TOF for nine FN measurement positions/orientations was significantly correlated to strength ( R 2  = 0.79) and FN cortical QCT variables: total BMD ( R 2  = 0.54); regional BMD in the inferoanterior ( R 2  = 0.90) and superoanterior ( R 2  = 0.57) quadrants; and moment of inertia ( R 2  = 0.71). The results of this study demonstrate that QUS can perform a targeted measurement of the FN cortical compartment. Because the method involves mechanical guided waves, the QUS variable is related to the geometric and material properties of the cortical shell (cortical thickness, tissue elasticity, and porosity). This work opens the way to a multimodal QUS assessment of the proximal femur, combining our approach targeting the cortical shell with the existing modality sensitive to the trabecular compartment. In vivo feasibility of our approach has to be confirmed with experimental data in patients. © 2013 American Society for Bone and Mineral Research